Multi-drug resistant tuberculosis burden and risk factors: An update - Marahatta, SB (Kathmandu University Medical Journal, 2010)
Multi-drug resistant (MDR) tuberculosis is defined as disease caused by Mycobacterium tuberculosis with resistance to at least two anti-tubercular drugs Isoniazid and Rifampicin. Recent surveillance data have revealed that prevalence of the drug resistant tuberculosis has risen to the highest rate ever recorded in the history. Drug resistant tuberculosis generally arises through the selection of mutated strains by inadequate therapy. The most powerful predictor of the presence of MDR-TB is a history of treatment of TB. Shortage of drugs has been one of the most common reasons for the inadequacy of the initial anti-TB regimen, especially in resource poor settings. Other major issues significantly contributing to the higher complexity of the treatment of MDR-TB is the increased cost of treatment. Other factors also play important role in the development of MDR-TB such as poor administrative control on purchase and distribution of the drugs with no proper mechanism on quality control and bioavailability tests. Tuberculosis control program implemented in past has also partially contributed to the development of drug resistance due to poor follow up and infrastructure. The association known for centuries between TB and poverty also applies to MDR-TB, a rather significant inverse association with MDR-TB. Various treatment strategies have been employed, including the use of standardised treatment regimens based upon representative local susceptibility patterns, empirical treatment based upon previous treatment history and local Drug Susceptibility Test (DST) patterns, and individualised treatment designed on the basis of individual DST results. Treatment outcomes among MDR-TB cases have varied widely; a recent survey of five Green Line Committee (GLC) approved sites in resource-limited countries found treatment success rates of 70%. Treatment continues to be limited in the resource poor countries where the demand is high. The ultimate strategy to control multidrug resistant tuberculosis is one that implements comprehensive approach incorporating treatment of multidrug-resistant tuberculosis based upon principles closely related to those of its general DOTS strategy for TB control: sustained political commitment; a rational case-finding strategy including accurate, timely diagnosis through quality assured culture and DST; appropriate treatment strategies that use second-line drugs under proper case management conditions; uninterrupted supply of quality-assured antituberculosis drugs; standardised recording and reporting system. Key words: DOTS Plus; Multi drug resistant (MDR) tuberculosis burden; risk factors. DOI: 10.3126/kumj.v8i1.3234 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 116-125